Role of nutrient supply in yield increase and quality improvement of spice pepper - B. Irinyi; J. Kapitány (International Journal of Horticultural Science, 2004)
Hungarian spice pepper powder is a unique product, a real hungaricum with its flavour and aroma compounds and seasoning effect. Its competitiveness with foreign spice peppers is ensured by its high biological value deriving from the specially Hungarian production and processing technology. Besides the traditional and highly manual labour intensive processing technology, there are some modern industrial technologies as well, where high quality can be guaranteed only by producing excellent base material (raw pepper pods). This is the reason which necessitates the rational development of the elements of the production technology, such as nutrient supply. Our objective was to offer a contribution to this aim by our trials in plant nutrition.